Strategic Alignment and Employee Perception in the Balanced Scorecard Implementation: a Performance Management Evaluation in Mining Division Toward World-Class Standards - Hidayat, Rahmat; Wibisono, Dermawan (Community Engagement and Emergence Journal (CEEJ), 2025)
The dynamic mining industry landscape requires organizations like PT Bukit Asam Tbk. (PTBA) to ensure robust strategic alignment to achieve world-class standards. This study investigates the perception gaps and alignment issues in the implementation of the Balanced Scorecard (BSC) within PTBA’s Mining Division. Three research questions guide this work: whether perception differences exist between management and executor levels regarding strategy execution; the gap between expected and actual realization of strategy; and the alignment between employee-perceived priorities and formal the BSC structures. The study applies a quantitative approach using Likert-scale surveys, gap analysis, and the Analytic Hierarchy Process (AHP). Statistical tools include descriptive analysis, Mann-Whitney U tests, Spearman correlation, and the AHP weight calculation. Results reveal notable perception gaps, particularly at the executor level, and significant differences between groups across all constructs. The AHP analysis indicates that internal business process and learning and growth perspectives are prioritized by employees, though misalignments with formal strategy remain. An implementation scenario is proposed through the Enhanced BSC Framework that includes phased strategic communication, dynamic KPI review using AHP, and integrated data-driven feedback systems. This study acknowledges several limitations, such as its single-case scope, the use of self-reported data, a limited observation period, and the absence of external benchmarking. This research contributes to performance management practices by highlighting the importance of aligning strategic priorities across organizational levels to support PTBA’s transformation journey.